Social Public Health System and Sustainability - Vuong, Quan-Hoang; Hong, Khuat Thu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This edited volume contains 18 articles published in Sustainability from late 2018 to early 2021. During that time, the world faced the fatal and widespread health crisis, COVID-19, which had threatened the social and public health systems at every corner for quite some time.As the Guest-Editors and also a contributing authors, we are glad that the academic contents from the Special Issue will now be put together in this volume, making the authors' hard work and efforts accessible to the larger audience.